A subtractive proteomics approach for the identification of immunodominant Acinetobacter baumannii vaccine candidate proteins - Acar, Mustafa Burak; Ayaz-Güner, Şerife; Güner, Hüseyin; Dinç, Gökçen; Ulu Kılıç, Ayşegül; Doğanay, Mehmet; Özcan, Servet (Frontiers in Immunology, 2022)
Background Acinetobacter baumannii is one of the most life-threatening multidrug-resistant pathogens worldwide. Currently, 50%–70% of clinical isolates of A. baumannii are extensively drug-resistant, and available antibiotic options against A. baumannii infections are limited. There is still a need to discover specific de facto bacterial antigenic proteins that could be effective vaccine candidates in human infection. With the growth of research in recent years, several candidate molecules have been identified for vaccine development. So far, no public health authorities have approved vaccines against A. baumannii. Methods This study aimed to identify immunodominant vaccine candidate proteins that can be immunoprecipitated specifically with patients’ IgGs, relying on the hypothesis that the infected person’s IgGs can capture immunodominant bacterial proteins. Herein, the outer-membrane and secreted proteins of sensitive and drug-resistant A. baumannii were captured using IgGs obtained from patient and healthy control sera and identified by Liquid Chromatography- Tandem Mass Spectrometry (LC-MS/MS) analysis. Results Using the subtractive proteomic approach, we determined 34 unique proteins captured only in drug-resistant A. baumannii strain via patient sera. After extensively evaluating the predicted epitope regions, solubility, transverse membrane characteristics, and structural properties, we selected several notable vaccine candidates. Conclusion We identified vaccine candidate proteins that triggered a de facto response of the human immune system against the antibiotic-resistant A. baumannii. Precipitation of bacterial proteins via patient immunoglobulins was a novel approach to identifying the proteins that could trigger a response in the patient immune system.